Clinical Manifestations Enticed in Clinical Cases of Canine Pyoderma - Shah, Bansari; Rao, Neha; Parikh, PV; Patel, DM; Nauriyal, DS (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Canine pyoderma is one of the most common causes of dermatitis with worldwide occurrence in small animal practice. The condition is diagnosed on the basis of clinical manifestations, isolation and identification of causative organisms by bacteriological cultural examination. A study was conducted on 130 dogs diagnosed with canine pyoderma presented at the Veterinary Clinical Complex (VCC), Veterinary College, Anand. These included cases of surface pyoderma (15), superficial pyoderma (50), deep pyoderma (32) and secondary pyoderma (33). The common clinical manifestations observed were exudation of pus, pruritus, erythema, pustules, papules, crusts, epidermal collarettes and alopecia. Canine pyoderma found secondary to other dermatological afflictions illustrated manifestations associated with the underlying cause. Hence, the condition should be differentially diagnosed and treated accordingly.